2018
DOI: 10.3389/fpsyt.2018.00372
|View full text |Cite
|
Sign up to set email alerts
|

A Mini Review on the Contribution of the Anterior Cingulate Cortex in the Risk of Psychosis in 22q11.2 Deletion Syndrome

Abstract: 22q11.2 deletion syndrome (22q11DS) is a neurogenetic disorder that causes a high risk of developing schizophrenia, thus representing a unique model for the investigation of biomarkers of psychosis. Cognitive and clinical risk factors have been identified as reliable predictors of schizophrenia in patients with 22q11DS and are currently used in the clinical practice. However, biomarkers based on neuroimaging are still lacking, mainly because of the analytic approaches adopted so far, which are almost uniquely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
(63 reference statements)
1
10
0
Order By: Relevance
“…In the present study we also examined CV, CT and SA between 22q11.2DS individuals with prodromal symptoms of psychosis compared to those without, and although we did not observe any differences potentially due to the small sample size, many previous studies have found that cortical regions implicated in idiopathic psychosis are also altered in 22q11.2DS. For example, alterations temporal and frontal regions have found to be predictive of positive symptoms in sub-threshold symptoms of psychosis 40 , 41 , prodromal symptoms of psychosis 42 , as well psychotic disorder 43 in 22q11.2DS. Further, a recent large scale study by the ENIGMA consortium suggest that there are convergent mechanisms contributing to CT changes in those who develop psychosis, both in carriers and non-carriers of the microdeletion 7 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we also examined CV, CT and SA between 22q11.2DS individuals with prodromal symptoms of psychosis compared to those without, and although we did not observe any differences potentially due to the small sample size, many previous studies have found that cortical regions implicated in idiopathic psychosis are also altered in 22q11.2DS. For example, alterations temporal and frontal regions have found to be predictive of positive symptoms in sub-threshold symptoms of psychosis 40 , 41 , prodromal symptoms of psychosis 42 , as well psychotic disorder 43 in 22q11.2DS. Further, a recent large scale study by the ENIGMA consortium suggest that there are convergent mechanisms contributing to CT changes in those who develop psychosis, both in carriers and non-carriers of the microdeletion 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, in the only two studies to date investigating a dynamic feature of brain function in 22q11DS -the variability of blood-oxygenation level dependent (BOLD) signals -we found widespread reductions in brain variability in 22q11DS (102), and reduced variability in the dorsal ACC in patients with higher prodromal psychotic symptoms (101). In general, aberrant function, but also structure of the ACC has been suggested as a neuroimaging marker for the development of psychosis in 22q11DS (65) and might reflect dysfunctional self-monitoring and salience processing, possible mechanisms for the emergence of psychosis (37).…”
Section: Introductionmentioning
confidence: 87%
“…However, whilst duration of both dACC/dlPFC and FPN was positively correlated with psychotic symptoms, it was reduced overall in 22q11DS compared to HCs. Converging evidence from both structural and functional MRI points towards altered connectivity of the ACC in individuals with 22q11DS and psychotic symptoms (20,76,80,101), reviewed in (65). Hence we suspected that the quality of the activations; i.e., the coupling with other networks, might be relevant for higher psychotic symptoms.…”
Section: Alterations In 22q11ds: Implication Of Cognitive and Emotional Brain Networkmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous reports provide evidence that the structural and functional connectivity of these brain states is altered in patients with 22q11DS (Padula et al, 2015, 2017b; Schreiner et al, 2014). In particular the dACC, which is a central node of the SN, has been found to be affected in 22q11DS using different neuroimaging modalities and alterations of this brain region have been suggested as a biomarker for psychosis in the disorder (Padula et al, 2018). Lower persistence control energy in these brain states in patients with 22q11DS may seem counterintuitive, as the healthy brain is assumed to decrement energy.…”
Section: Discussionmentioning
confidence: 99%